Modelling Cancer in Drosophila: Exploration to Personalised Medicine. - Badmos, H.; Cagan, R. (Advances in Experimental Medicine and Biology, 2025)
Drosophila has become an increasingly useful model for cancer research, providing a whole-animal platform to study tumour biology and screen potential therapies. This review highlights its advantages, including genetic tools and patient-specific fly avatars that allow modelling of human cancer genotypes and high-throughput drug screening. Key successes include insights into metastatic mechanisms and the identification of effective drug combinations as personalised therapies, exemplified by fly-to-bedside studies. We also explore the concept of chemical evolution, where Drosophila guides multi-target drug discovery, showing promise for 'network-based' therapies that address cancer complexity.